2013
DOI: 10.5539/ies.v6n11p35
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Relations between Life Satisfaction, Burnout, Work Engagement and Hopelessness of High School Students

Abstract: The purpose of this research is to determine the relations between high school students' life satisfaction, burnout, work engagement and hopelessness scores and examine the contribution of their burnout, work engagement and hopelessness scores in the prediction of their life satisfaction scores. The Satisfaction with Life Scale (SWLS), Maslach Burnout Inventory-Student Survey (MBI-SS), Utrecht Work Engagement Scale-Student Survey (UWES-SS), Beck Hopelessness Scale (BHS) and "Personal Information Form", has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
3
10
0
Order By: Relevance
“…In addition to this, in the context of the criterion related validity study of the scale, negative directional statistically significant relationships were found between the MBI-SF subscales, adapted by Çapri et al (2013) and the UWES-SF subscales, the values for the long form are between -.31 and -.60; and for the short form between -.27 and -.59. These acquired results can be seen as similar to the results of the study where a significant relationship between UWES-SF and MBI-SF was found in the context of criterion related validity studies (Çapri, et al, 2013;Kutsal, 2009;Schaufeli & Bakker, 2004;Schaufeli, Martinez et al, 2002; and can be said to support the theoretical explanation that work engagement is the positive opposite of burnout. On the other hand, while the vigor and dedication subscales were expressed as the main dimensions of work engagement; exhaustion and cynicism were expressed as the main factors of burnout (Maslach, Schaufeli, & Leiter, 2001;Schaufeli & Bakker, 2004), the efficacy subscale was said to reflect a more personal quality rather than burnout (Cordes & Dougherty, 1993, as cited in Schaufeli & Salanova, 2007), and the absorption subscale was said to be a result of these main factors (Langelaan et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition to this, in the context of the criterion related validity study of the scale, negative directional statistically significant relationships were found between the MBI-SF subscales, adapted by Çapri et al (2013) and the UWES-SF subscales, the values for the long form are between -.31 and -.60; and for the short form between -.27 and -.59. These acquired results can be seen as similar to the results of the study where a significant relationship between UWES-SF and MBI-SF was found in the context of criterion related validity studies (Çapri, et al, 2013;Kutsal, 2009;Schaufeli & Bakker, 2004;Schaufeli, Martinez et al, 2002; and can be said to support the theoretical explanation that work engagement is the positive opposite of burnout. On the other hand, while the vigor and dedication subscales were expressed as the main dimensions of work engagement; exhaustion and cynicism were expressed as the main factors of burnout (Maslach, Schaufeli, & Leiter, 2001;Schaufeli & Bakker, 2004), the efficacy subscale was said to reflect a more personal quality rather than burnout (Cordes & Dougherty, 1993, as cited in Schaufeli & Salanova, 2007), and the absorption subscale was said to be a result of these main factors (Langelaan et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…In the direction of the primary objective of this study, which was to conduct the adaptation, validity and reliability studies of UWES-SF's long (17 items) and short (9 items) forms and 3 factor analyses on the high school students of our country; the findings regarding the adaptation, validity and reliability studies showed that both of the forms had sufficient levels of valid and reliable qualities and that both single factor and three factor structures were confirmed. It can be said that the acquired results are consistent with some local (Çapri et al, 2013;Kutsal, 2009) and international (Schaufeli & Bakker, 2004;Schaufeli, Martinez et al, 2002; research findings in the literature.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Aypay (2011) studied primary school students. Kutsal (2009); Aypay and Eryılmaz (2011a, 2011b); Sever and Aypay (2011); Aypay (2012); Çapri, Gündüz, and Akbay (2013); and Yedigöz, Sönmez, and Çapri (2013) studied high school students. Çapri, Gündüz, and Gökçakan (2011); Gündüz, Çapri, and Gökçakan (2012); and Çapri (2013) examined university students' burnout.…”
mentioning
confidence: 99%